Encyclopedia of communication theory - Littlejohn, Stephen W.; Foss, Karen A. (2009)
The Encyclopedia of Communication Theory provides students and researchers with a comprehensive overview of contemporary communication theory. Reference librarians report that students frequently approach them seeking a source that will provide them with a quick overview of a particular theory or theorist - just enough to help them grasp the general concept or theory and its relation to the discipline as a whole